COVID-19 Vaccination in Pediatric Population: A Necessity or Obstruction to the Protection of the Right to Health? Biojuridical Perspective - Bilotta, Clio; Perrone, Giulio; Zerbo, Stefania; Argo, Antonina (Frontiers in Public Health, 2022)
One of the most recently debated topics worldwide is the mass vaccination of children against coronavirus disease 2019 (COVID-19). Next, the risk/benefit ratio of COVID-19 vaccination and infection in children are compared. Nonetheless, the real question in this debate is as follows: Does the vaccine represent a necessary tool or is it an obstacle in protecting the right to health? From a public health point of view, the Supreme Court of Nova Scotia, in Canada, recommends COVID-19 vaccination in the pediatric population. Based on Article 25 of the Draft Articles on State responsibility, vaccination can be considered a social act necessary for protecting the individual's right to health. The 1989 New York Convention on the Rights of the Child and the European Regulation number 219/1111 state that the opinion of a minor aged >12 years is considerable. However, this validity of opinion is related to age and degree of discernment. The onset of adverse events following the administration of the COVID-19 vaccine may lead to compensation in the near future. Recent studies have identified a new COVID-19-related pediatric pathology, known as multisystem inflammatory syndrome. Other studies have demonstrated that myocarditis in the pediatric population might occur following COVID-19 vaccine administration. In June 2021 in the USA, the Center for Control and Prevention of Infectious Diseases Advisory Committee on Immunization Practices declared that the benefits of vaccination against COVID-19 in the pediatric population outweighed the risks. In the meantime, whereas the bioethical debate remains open, monitoring the real risk/benefit ratio of vaccination in the pediatric population is crucial.